Protecting human rights and upholding international humanitarian law amid the war in Ukraine - Rudnytska, Olha; Zlakoman, Ihor; Podilchak, Olha; Vitenko, Zakhar; Khrust, Dmytro (Universidad Hemisferios, 2025)
When evaluating the relationship between humanitarian law that only involves armed conflicts and human rights that apply in peacetime and war, the main question is whether the protections provided to persons under the latter are less than those under the former. The paper explores the many facets of this issue, including the general interplay between humanitarian law and human rights law, the applicability of specific human rights in the context of armed conflicts, among more, using the example of the war in Ukraine. The methodological toolkit includes a systemic-structural approach, generalization, the method of scientific abstraction, and the method of logical and systemic analysis. The article has shown little evidence to support the preconceived notion that humanitarian law can supersede human rights law, since it is lex specialis. Likewise, it is demonstrated that human rights and humanitarian law norms disclose a comparable substance when humanitarian law protections are enforced as required by their content. In some situations, the protection provided by human rights legislation is equal to or greater than that provided by humanitarian principles; however, the inherent constraints of human rights treaty norms allow for considering humanitarian law's criteria for proportionality, humanity, and military necessity. Therefore, the International Criminal Court's (ICC) capabilities and potential to assess violations of international humanitarian law (IHL) during the war in Ukraine and the prospects for issuing binding decisions are assessed. Overall, the study asserts that the war in Ukraine can serve as an important precedent for the development of IHL and its implementing principles.